Diffusely Metastasized Adenocarcinoma Arising in a Mucinous Carcinoid of the Ovary: A Case Report. (May 2018) - Van Rompuy, Anne-Sophie; Vanderstichele, Adriaan; Vergote, Ignace; Moerman, Philippe
Abstract : Mucinous (goblet cell) carcinoids are a rare type of ovarian carcinoid tumors. Only a limited number of primary mucinous carcinoids of the ovary have been reported in the literature. We describe the case of a 55-year-old woman with a diffusely metastasized adenocarcinoma arising in a primary ovarian mucinous carcinoid. The differential diagnosis with a metastatic goblet cell carcinoid from the appendix or elsewhere can be very challenging. In our case, especially the immunohistochemical profile of the tumor with diffuse positivity for cytokeratin 7 and PAX8, and no expression of cytokeratin 20 and CDX2, directed us toward a primary ovarian origin. Expression of PAX8 in ovarian mucinous carcinoid has never been reported before.